2018
DOI: 10.1063/1.5037678
|View full text |Cite
|
Sign up to set email alerts
|

Bandgap engineering of α-(AlxGa1-x)2O3 by a mist chemical vapor deposition two-chamber system and verification of Vegard's Law

Abstract: This work reports growth of α-(AlxGa1-x)2O3 single crystals with high incorporation of Al by a Mist Chemical Vapor Deposition two-chamber system, which was rationally designed to avoid side-reactions between different precursors during solution preparation for multi-component thin film growth. Multiple acceleration voltages were used in Energy Dispersive X-ray measurements to reliably obtain the Al composition x of the films. As a result, Vegard's law for lattice constants was verified and found to be valid in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 37 publications
6
72
0
Order By: Relevance
“…The constants derived for the α‐(AlxGa1x)2normalO3 thin films coincides for 0x0.55 with literature values [ 25,28 ] and follow Vegard's law. The transition to pseudomorphic growth at around x=0.55 is influenced by the thin‐film thickness (here 240 nm) and will occur at higher Al concentrations for thicker thin films.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The constants derived for the α‐(AlxGa1x)2normalO3 thin films coincides for 0x0.55 with literature values [ 25,28 ] and follow Vegard's law. The transition to pseudomorphic growth at around x=0.55 is influenced by the thin‐film thickness (here 240 nm) and will occur at higher Al concentrations for thicker thin films.…”
Section: Resultssupporting
confidence: 85%
“…In contrast to this current study, Ito et al, Dang et al, and Fujita et al reported growth of relaxed α‐(AlxGa1x)2normalO3 thin films in the entire composition range, pseudomorphic growth was not. [ 25,28,38 ] Grundmann et al reported a similar transition composition for thin films in r‐plane sapphire, which might be due to different relaxation mechanisms, e.g., for (01.2)‐oriented thin films relaxation may occur via prismatic glide planes which is not possible for the (11.0)‐oriented thin films discussed here.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…(Al x Ga 1−x ) 2 O 3 has shown unique properties including enhanced predicted breakdown strength with an improved chemical and thermal stability [10,11], making it highly desirable for high power electronics and deep ultraviolet optical applications [9,12]. The bandgap in (Al x Ga 1−x ) 2 O 3 tends to increase monotonically with the incorporation of Al content [12,13] that forms (Al x Ga 1−x ) 2 O 3-/Ga 2 O 3 heterostructures with large band offset [9]. This elevated bandgap has enabled successful realization of (Al x Ga 1 −x ) 2 O 3 based field-effect transistors [11,14,15,16], Schottky barrier diodes [17,18], and photodetectors [19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the similar electronic structure of Ga and Al with Al 2 O 3 exhibiting a higher bandgap [9], it was possible to widen the bandgap of shown unique properties including enhanced predicted breakdown strength with an improved chemical and thermal stability [10,11], making it highly desirable for high power electronics and deep ultraviolet optical applications [9,12]. The bandgap in (Al x Ga 1−x ) 2 O 3 tends to increase monotonically with the incorporation of Al content [12,13] that forms (Al x Ga 1−x ) 2 O 3-/Ga 2 O 3 heterostructures with large band offset [9]. This elevated bandgap has enabled successful realization of (Al x Ga 1 −x ) 2 O 3 based field-effect transistors [11,14,15,16], Schottky barrier diodes [17,18], and photodetectors [19,20,21].…”
Section: Introductionmentioning
confidence: 99%